INTELLECTUAL CAPITAL, RISK, DAN FINANCIAL PERFORMANCE MAQASHID BANK SYARIAH YANG TERDAFTAR DI OJK - Yuyun Ristianawati; Setyo Budi Hartono (ITB AAS Indonesia Surakarta, 2026)
The development of “Sharia banking in Indonesia demonstrates only a limited significance with reference to the expansion of businesses. By underlining the significance of innovation and intellectual capital (IC) management, human resource management has an impact on the competitiveness of Sharia banks, which are dependent on a workforce that is knowledge-based. Both the risk profile and the performance of Sharia banks are influenced by intellectual capital, which can be defined as the knowledge, information, intellectual property, and experience that contribute to the generation of wealth. For the purpose of this study, a quantitative methodology was utilized to conduct an analysis of twelve Sharia banks that were registered with the Financial Services Authority (OJK). Secondary data and regression analysis were utilized. The findings suggest that the variable known as Maqashid Sharia Performance (MSI) is significantly impacted in a negative manner by the implementation of VACA. When it comes to MSI, Value Added Human Capital (IB-VAHU) has a beneficial impact, although it is not particularly important. IB-STVA, which stands for structural capital, has a negative impact on MSI that is not considerable. The Capital Adequacy Ratio (CAR) has a detrimental impact on MSI, but an effect that is not significant. There is a relationship between the Loan-to-Deposit Ratio (LDR) and MSI that is favorable but not significant. In conclusion, the value of the adjusted R-squared (R2) is 0.225, which indicates that the Intellectual Capital variables (IB-VACA, IB-VAHU, and IB-STVA) and bank risks (capital risk and liquidity risk) collectively explain 22.5% of the variance in Maqashid Sharia Performance (MSI), while other factors account for the remaining 77.5% of the variance.”